The contribution of energy systems during 15-second sprint exercise in athletes of different sports specializations - Archacki,Damian; Zieliński,Jacek; Pospieszna,Barbara; Włodarczyk,Michał; Kusy,Krzysztof (PeerJ, 2024)
Background Long-term adaptations and ongoing training seem to modify the energy system contribution in highly trained individuals. We aimed to compare the energy metabolism profile during sprint exercise in athletes of different specialties. Methods Endurance (n = 17, 20.3 ± 6.0 yrs), speed-power (n = 14, 20.3 ± 2.5 yrs), and mixed (n = 19, 23.4 ± 4.8 yrs) athletes performed adapted 15-second all-out test before and after a general preparation training period. The contribution of phosphagen, glycolytic, and aerobic systems was calculated using the three-component PCr-LA-O2 method. Results Between-group differences were observed in the contribution of energy systems in the first and second examinations. The proportions were 47:41:12 in endurance, 35:57:8 in team sports, and 45:48:7 in speed-power athletes. Endurance athletes differed in the phosphagen (p < 0.001) and glycolytic systems (p = 0.006) from team sports and in the aerobic system from speed-power athletes (p = 0.003). No substantial shifts were observed after the general preparatory phase, except a decrease in aerobic energy contribution in team sports athletes (p = 0.048). Conclusion Sports specialization and metabolic profile influence energy system contribution during sprint exercise. Highly trained athletes show a stable energy profile during the general preparation phase, indicative of long-term adaptation, rather than immediate training effects.
Keywords: Glycolysis; Phosphagen system; Aerobic metabolism; Wingate test; All-out effort; Long-term adaptation